Heat-Seal Strength Analysis Of Laminated Films With LLDPE And LDPE Sealant Materials In Bar Sealing Application - Hassan, Azman; Cheng, See Yuan; Ghazali, Mohd Imran; Ismail, Ahmad Fauzi (2006)
The heat-seal strength and failure modes of laminated films with Linear Low Density Polyethylene (LLDPE) and Low Density Polyethylene (LDPE) as the sealant materials were investigated. Heat-seal strength increases with platen temperature for all samples. The maximum achievable heat-seal strength for laminated film using LDPE and LLDPE as sealant material is 0.598 N/mm and 4.02 N/mm, respectively. Four failure modes were observed, namely, the peeling mode, tearing mode, delamination mode and combination of tearing and delamination mode failures. Strength of heat-seal and its failure modes are closely related. Heat-seal strength achieved under tearing mode failure is the highest, follow by heat-seal strength achieved under delamination mode failure, and the heat-seal strength achieved under peeling mode failure is the lowest. Corresponding platen temperature TC and heat-seal strength SSC where acceptable heat-seal begins to be made weree 118, 114 and 108 ºC, and 2.82, 2.38 and 0.48 N/mm for sample #1, #2 and #3, respectively.